Exploration Of Antioxidants Effects On The Crude Eps Extraction From Marine Actinomycetes Of Saccharopolyspora - Arun Kishore Rn; Dr. Dinesh Kumar (Revista Electronica de Veterinaria)
Periodontitis is a chronic inflammatory disease driven by microbial plaque and an excessive host immune response, leading to tissue destruction and an imbalance between reactive species and antioxidants. While conventional periodontal therapy remains the primary treatment, adjunctive antimicrobial and antioxidant agents may enhance therapeutic outcomes. This study evaluates the antioxidant activity of exopolysaccharide (EPS) crude extract from Saccharopolyspora, a genus of actinomycetes known for its bioactive properties. The antioxidant potential was assessed through Total Antioxidant Activity, DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenging assay, and Total Reducing Property at varying concentrations of the crude extract. The results showed a dose-dependent increase in antioxidant activity, with the highest activity observed at 100% concentration (58% for Total Antioxidant Activity and 48% for both DPPH Activity and Total Reducing Property). These findings suggest that Saccharopolyspora-derived EPS possesses significant antioxidant potential, making it a promising candidate for therapeutic applications in periodontal treatment and beyond. Further research is needed to explore its antimicrobial, anti-inflammatory, and regenerative properties.